Focus on economy or ecology? A three‐dimensional trade‐off based on ecological carrying capacity in southwest China. (4th December 2018) - Peng, Li; Deng, Wei; Zhang, Hao; Sun, Jian; Xiong, Junnan
Abstract: Economic growth and human activities challenge the regional harmony of the economy and environment. Based on an evaluation of ecological carrying capacity (ECC), we have constructed a three‐dimensional trade‐off model for socially harmonious development for the Sichuan and Yunnan regions in southwest China. The results demonstrate that there is a continuous increase in socioeconomic coordination (SEC; slope > 0.23) and a change in the ECC in the study area, characterized by subtle fluctuations from 2000 through 2008. This was primarily due to the loss of resource and environment carrying capacity wiping out the profits of SEC. Significant government aid during the postdisaster reconstruction and more attention being paid to the environment in policy resulted in a faster increase in ECC (slope > 0.38) from 2008 to 2016. Based on this trade‐off model, managers could deeply understand the relationship between resources, the economy, and ecology. Summary for Managers Ecological environment protection is increasingly crucial in Sichuan and Yunnan regions as they feel the effects of climate change and human activities. The three‐dimensional trade‐off model measuring socially coordinated development is a modified multiobjective, decision‐making model. Based on this trade‐off model, managers could, understand the relationship between resources, the economy, and ecology. It can help manage our environmental assets and plan ecological conservation, to ensure that the environment maintains its capacity to serve the societal development.